Rational choice of oil supply pressure, feeder diameter and it’s arrangement for hybrid Reyleigh step bearing. - Хлопенко, Н.Я.; Сорокина, Т.Н. (Problems of Tribology, 2016)
The geometrical and operation conditions of the feeder are the main problem of the hydrostatodynamic (hybrid) bearing optimal characteristics selection. Supercharge pressure change at the step bearing lubrication supply is one of the most important operation characteristic. The feeder diameter change and it’s arrangement along the feeder groove mean much to geometrical characteristics. The main aim of the article is to determine the influence of the feeder along the feeder groove, feeder diameter and the supercharge pressure change on the static characteristics by the different rotor rotation of hybrid bearing. Our calculations gives the positive result, notably, the supercharge pressure change considerable improve the hy-brid bearing static characteristics. The feeder diameter change at the different operating clearances and it’s arrangement along feeder groove gives the possibility to determine its optimal characteristics and arrangement. As evident from researches the big feeder diameter brings the static characteristics degradation to the hybrid bearing. The optimization of the geometrical and regimes features was carried out at the turbulent regime including the lubrication temperature and viscosity parameters. As a result of calculations for feeder optimization there were determined the following evidences – lubrication tem-perature, which are not exceed the critical value for the present oil and provided acceptable step- bearing exploitation fea-tures. The results can become the basic part for the further hybrid bearing design.